ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KONSUMSI FAST FOOD PADA REMAJA - Sabir Sabir; Hermansyah Hermansyah; Atik Sunarmi; Firman Fajar Perdhana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
One of the health impacts often associated with excessive fast food consumption is an increased risk of obesity. The high rate of fast food consumption in the community is influenced by various interrelated factors, including both individual and environmental factors. The study design used in this research was cross-sectional. The study was conducted at SMPN 30 Makassar. The research was carried out in July 2025. The study population consisted of all students enrolled at SMPN 30 Makassar. The sample comprised 95 respondents. The sampling technique used was stratified random sampling. The research instrument used a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicate a significant association between knowledge (p-value: 0.000) and peer influence (p-value: 0.038) with fast food consumption behavior among students. It is recommended that parents not allow their children to buy fast food at school or reduce the frequency of fast food consumption, and not give their children excessive pocket money to buy fast food. Additionally, peers should refrain from influencing or encouraging the purchase of fast food at school.Keywords: Fast Food, Knowledge, Peers.